Effects of Different Levels of Feed Restriction on Nitrogen Intake and Excretion from Male Bean Goats in Tropical Areas - Tahuk, Paulus Klau (Universitas Veteran Bangun Nusantara, 2024)
The study aimed to determine the intake and nitrogen excretion of male Peanut goats fed different feed restrictions. The study was conducted for three months at the livestock experimental barn of the Faculty of Agriculture, Science and Health, University of Timor, in Kefamenanu, North Central Timor District, Indonesia. A total of 9 (nine) male Kacang goats with initial body weights ranging from 9 to 13 kg and ages between 12 to 14 months were divided into three groups, each representing a different treatment. The animals were given 3 (three) treatments, each treatment T0: goats without feed restriction; T1: goats were given 100% feed restriction according to basic living needs; and T2: goats were restricted to feed only 50% of basic living needs. The results showed that the average nitrogen consumption of each treatment was T1 at 3.50 g/head/day, T1 at 3.09 g/head/day, and T2 treatment at 3.24 g/head/day. Fecal nitrogen excretion of T0 treatment was 1.24 g/head/day; T1 treatment was 1.61 g/head/day, and T2 treatment was 1.77 g/head/day. While the urinary nitrogen excretion of each treatment was T0 treatment of 0.35 g/head/day, T1 treatment of 0.64 g/head/day, and T2 treatment of 1.09 g/head/day, it can be concluded that feed restriction can reduce nitrogen consumed compared to animals that receive normal feed. In contrast, nitrogen excreted through feces and urine increased in livestock that experienced feed restriction of 100% of the basic diet and 50% of the basic diet.